War Studies at the School of Histories and Humanities - School of Histories and Humanities (Trinity College Dublin, 2007)
The School of Histories and Humanities at Trinity is the leading centre for war studies in Ireland. It has particular expertise in the history of the First World War, the Second World War and Irish conflicts. The School also offers expertise on warfare in Elizabethan Ireland and on medieval warfare. In addition, the School offers courses on the history of the Second World War in France, Britain and Russia. The War of Independence, the Irish Civil War and the Northern Troubles are also central teaching and research areas within the School with the Centre for Contemporary Irish History carrying out pioneering work on these subjects, led by Professor Eunan O'Halpin in conjunction with a specialised post-doctoral team.
Exhibited at the second Glucksman Memorial Symposium on June 13th 2007
Keywords: War Studies; School of Histories and Humanities, Trinity College Dublin; First World War